HAKIKAT EKONOMI ISLAM TENTANG KELANGKAAN SUMBER DAYA EKONOMI DAN KEBUTUHAN MANUSIA (ERA GLOBALISSASI DAN INDUSTRIALISASI) - Rahmad Annam (Institut Agama Islam Negeri Padngsidimpuan, 2016)
Essensce islamic economy based ability in complying need economy, that is teoritical scarcity. Explain that condition human resource inadequate for complete or satisfactory all need human. Impact globalization and industriliazation take along alteration attitude and behavior human to need human and want its. Behavior consumtive penetrate joint life society. between goods primery and secondary to be trend in measurement successfulness and stability social, increasing revenue per capita. Resident always caused measurement successfulness and welfare in concept economiy building. Occured it ekspolitation and modification. Frequently based on for aim increasing welfare social. The consequence occurred crisis multidimensional regarding contuity human resource in assure continuance creature surface earth.